The Effects of Cupping Therapy on Biomechanical Properties in Wistar Rat Skin - Traneh Norozali; Mohammad Mohsen Roostayi; Farideh Dehghan Manshadi; Mehdi Abbasi; Alireza Akbarzadeh Baghban; Mohammad Reza Khaleghi (Vesnu Publications, 2013)
Introduction: In most Asian countries, cupping therapy has been used as a therapeutic method for soft tissue lesions but there is no high quality evidence-based support for its clinical efficacy. Cupping therapy may have an influence on the biomechanical properties of the tissues under treatment. Therefore, the current study was intended to investigate the effects of cupping therapy on some biomechanical properties of the skin such as stiffness and ultimate tensile strength in Wistar rats. Materials and Methods: In this experimental study, the convenience non-probability sampling method was used to collect 20 rats (10 rats in experimental group and 10 rats in pure control group) from the animal laboratory of Tehran University's Anatomy Department. The rats were divided into experimental, experimental control and pure control groups. In the experimental group, the animals' skins were cupped 10 minutes a day for 12 days. Skin stiffness and its ultimate tensile strength were measured in all groups using a tensiometer. For statistical analyses, paired sample t-test was used to compare the skin of both sides of the experimental animals' body while the independent sample t-test was adopted to compare between-group scores. Results: Compared to experimental control (P = 0.048, P = 0.029) and pure control (P = 0.018, P = 0.008) groups, skin stiffness and skin ultimate tensile strength of the experimental group (cupped group) decreased significantly. Conclusion: Cupping therapy can result in changes in biomechanical properties of the skin, namely stiffness and ultimate tensile strength reduction. Key words: Cupping therapy, Stiffness, Ultimate tensile strength, Wistar